Efficacy of Curcumin on Aortic Atherosclerosis: A Systematic Review and Meta-Analysis in Mouse Studies and Insights into Possible Mechanisms. (9th January 2020) - Lin, Ke; Chen, Huaijun; Chen, Xiaojun; Qian, Jinfu; Huang, Shushi; Huang, Weijian
Abstract : Since the first report in 2005, accumulating interests have been focused on the effect of curcumin in atherosclerosis with discrepancies. Therefore, we conducted a systematic review and meta-analysis to comprehensively estimate its effect against atherosclerosis. Literature search was performed on the database of PubMed, EMBASE, and Cochrane Library to identify relevant studies which estimated the effect of curcumin in atherosclerosis. Reporting effects on aortic lesion area was the primary outcome while effects on serum lipid profiles and circulating inflammatory markers were the secondary outcome. A total of 10 studies including 14 independent pairwise experiments were included in our analysis. We clarified that curcumin could significantly reduce aortic atherosclerotic lesion area (SMD = ‐ 0.89, 95% CI: -1.36 to -0.41, P = 0.0003 ), decrease serum lipid profiles (Tc, MD = ‐ 1.005, 95% CI: -1.885 to -0.124, P = 0.025 ; TG, MD = ‐ 0.045, 95% CI: -0.088 to -0.002, P = 0.042 ; LDL-c, MD = ‐ 0.523, 95% CI: -0.896 to -0.149, P = 0.006 ) as well as plasma inflammatory indicators (TNF- α, MD = ‐ 56.641, 95% CI: -86.848 to -26.433, P < 0.001 ; IL-1 β, MD = ‐ 5.089, 95% CI: -8.559 to -1.619, P = 0.004 ). Dose-response meta-analysis predicted effective dosage of curcumin between 0 and 347 mg/kg BW per day, which was safe and nontoxic according to the existing publications. The underlying mechanisms were also discussed and might be associated with the modulation of lipid transport and inflammation in cells within artery walls as well as indirect modulations in other tissues. Clinical evidence from nonatherosclerosis populations revealed that curcumin would lower the lipid profiles and inflammatory responses as it has in a mouse model. However, standard preclinical animal trial designs are still needed; further studies focusing on the optimal dose of curcumin against atherosclerosis and RCTs directly in atherosclerosis patients are also warranted.